Critical Appraisal - Prof. Dr. S. Akhtar Hussain Bokhari (Journal of University Medical & Dental College, 2020)
Research is exponentially increasing around the world and “new” up-to-the-minute information is constantly replacing or improving upon “old news”. Clinicians, researchers, educationists find themselves in less and less time to find and utilize “new information”. Selection, reading and application of new research becomes more burdening when researchers report conflicting results on the same issue or present different modalities to solve a single problem. However for a successful professional, it is necessary that one must remain up to date in one’s field.